2017
DOI: 10.1177/2010105817738794
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting postoperative pain and delay in discharge from the post-anaesthesia care unit: A descriptive correlational study

Abstract: Background: Pain occurring in the post-anaesthesia care unit (PACU) is common, distressing to patients and remains a management challenge for staff. This study aims to identify the factors affecting pain severity and delay in discharge of patients from the PACU. Methods: Data from 590 consecutive postoperative patients in the PACU was collected over one month in 2012 at the Singapore General Hospital. Patient demographics, surgical, intraoperative anaesthetic and recovery data were collected. The primary outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
2
10
2
Order By: Relevance
“…Similarly, our study result was higher than the studies conducted in Singapore (32.2%), Eastern Poland (59%), Dutch (41%), South Africa 62 %, and Mekelle (30.5%), (7,9,(15)(16)(17)(18). This variation may be due to differences in infrastructure, a postoperative pain management protocol, sample size, and pain assessment time.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Similarly, our study result was higher than the studies conducted in Singapore (32.2%), Eastern Poland (59%), Dutch (41%), South Africa 62 %, and Mekelle (30.5%), (7,9,(15)(16)(17)(18). This variation may be due to differences in infrastructure, a postoperative pain management protocol, sample size, and pain assessment time.…”
Section: Discussioncontrasting
confidence: 72%
“…Advances in pharmacology, techniques, and education are making major inroads into the management of postoperative pain (5). Post-operation pain intensity is associated with variables like patient age, sex, type of surgery, anesthesia, duration of surgery and previous pain experience of the patient are some of the factors associated with moderate to severe postoperative pain development (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…5 Chan et al identified higher body mass index; abdominal, spine and superficial surgeries; use of general anesthesia; moderate to severe pain score; and use of nurse controlled analgesia as factors that delay discharge from PACU. 9 Imasogie and Chung in 2002 classified the risk factors for prolonged PACU stay after ambulatory surgery into preoperative, intraoperative, and postoperative. The preoperative risk factors included the type of surgery, pre-existing congestive heart failure, and increasing age.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Persistent acute pain leads to prolonged recovery, to delayed discharge from the hospital, and to higher re-admission rates, which can significantly increase the costs of treatment [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%